Controle jurisdicional do processo de impeachment: o impeachment da presidenta Dilma Rousseff perante o Supremo Tribunal Federal - Almir Megali Neto (2020)
This research has as its object the way by which the highest institution of the Brazilian Judicial Power, the Brazilian Supreme Court, exercised the judicial review of the impeachment process against the president Dilma Rousseff. Specifically, the Part I dedicates to recover the assumptions of legitimacy of judicial review of the impeachment process assumed by the Court itself throughout its institutional history. Assumptions that gave own characteristics to impeachment in Brazilian constitutionalism and that throughout the republican era were and still are object of strong opposition by part of the national legal doctrine. In Part II, are analyzed the main decisions of the Brazilian Supreme Court in the cases related to the impeachment process of the president Dilma Rousseff. It is made an analysis of the opinions of the justices of the Brazilian Supreme Court in this emblematic case, and pinpointing the contradictions and mistakes made by them, regarding the historical comprehension of the Court and of the brazilian republican tradition of the judicial review of the impeachment process.